Molecular Pathogenesis of Cholangiocarcinoma - G. Fava; I. Lorenzini (International Journal of Hepatology)
Epidemiological data from the last years show an increasing trend of incidence and mortality of cholangiocarcinoma (CC) worldwide. Many pathophysiologic aspects of this neoplasia are still unknown and need to be fully discovered. However, several progresses were recently made in order to establish the molecular mechanisms involved in the transformation and growth of malignant cholangiocytes. The principal concept that at least seems to be established is that cholangiocarcinogenesis is a multistep cellular process evolving from a normal condition of the epithelial biliary cells through a chronic inflammation status ending with malignant transformation. The bad prognosis related to CC justifies why a better identification of the molecular mechanisms involved in the growth and progression of this cancer is required for the development of effective preventive measures and valid treatment regimens. This Paper describes the scientific progresses made in the last years in defining the molecular pathways implicated in the generation of this devastating disease.